The social and cultural importance of high Andean wetlands: Addressing the stewardship approach for wetland management - Morocho Cuenca, J. (2017)
The Ramsar Convention on Wetlands encourages a stewardship approach for wetlands management, incorporating local communities in land management and conservation efforts. Understanding local interactions and perceptions of wetlands and primary causes of wetland degradation are required for any successful management plan. Plans should consider that communities or conservation areas are not homogenous and multiple user groups define conservation goals differently. This paper uses semi-structured interviews and participatory mapping to examine how ethnically diverse communities interact with a proposed Ramsar designation wetland system in Ecuador. This research sought to explore locals associations with the wetlands and their views of prominent conservation disturbances occurring in the area. Communities are affected by limited mobility due to the geographic nature of the region, which has affected their interaction with and understanding of the wetlands and shaped economic development in the region. Currently, road development, more than any other disturbance, will determine the future of the wetland, opening to the region for economic development or creating and understanding for the need to care for the crucial water source in the region. The paper concludes with implications for additional political ecology research in dynamic mountain environments and implications for local stewardship and sustainable development initiatives.